Advances in quantum chemistry. - Sabin, John R.; Brandas, Erkki (Advances in quantum chemistry, 2008)
Advances in Quantum Chemistry presents surveys of current developments in this rapidly developing field that falls between the historically established areas of mathematics, physics, chemistry, and biology. With invited reviews written by leading international researchers, each presenting new results, it provides a single vehicle for following progress in this interdisciplinary area. This volume concerns the proceedings of the 4th International Conference on the DV-Xa Method. The focus is on key issues of materials science, surfaces, boundaries, defects, metals, ceramics and organic materials and spectroscopy. The DV-Xa method is a Density Functional-like development, which has reached an unparalleled theoretical and practical sophistication in Japan and Korea. * publishes articles, invited reviews and proceedings of major international conferences and workshops * written by leading international researchers in quantum and theoretical chemistry * highlights important interdisciplinary developments.